Alcohol Intake Is Associated With Elevated Serum Levels of Selenium and Selenoprotein P in Humans - Isobe, Yuki; Asakura, Hiroki; Tsujiguchi, Hiromasa; Kannon, Takayuki; Takayama, Hiroaki; Takeshita, Yumie; Ishii, Kiyo-aki; Kanamori, Takehiro; Hara, Akinori; Yamashita, Tatsuya; Tajima, Atsushi; Kaneko, Shuichi; et al. (Frontiers in Nutrition, 2021)
Selenoprotein P is a hepatokine with antioxidative properties that eliminate a physiologic burst of reactive oxygen species required for intracellular signal transduction. Serum levels of selenoprotein P are elevated during aging and in people with type 2 diabetes, nonalcoholic fatty liver disease, and hepatitis C. However, how serum levels of full-length selenoprotein P are regulated largely remains unknown, especially in the general population. To understand the significance of serum selenoprotein P levels in the general population, we evaluated intrinsic and environmental factors associated with serum levels of full-length selenoprotein P in 1183 subjects participating in the Shika-health checkup cohort. Serum levels of selenium were positively correlated with liver enzymes and alcohol intake and negatively correlated with body mass index. Serum levels of selenoprotein P were positively correlated with age, liver enzymes, and alcohol intake. In multiple regression analyses, alcohol intake was positively correlated with serum levels of both selenium and selenoprotein P independently of age, gender, liver enzymes, and fatty liver on ultrasonography. In conclusion, alcohol intake is associated with elevated serum levels of selenium and selenoprotein P independently of liver enzyme levels and liver fat in the general population. Moderate alcohol intake may exert beneficial or harmful effects on health, at least partly by upregulating selenoprotein P. These findings increase our understanding of alcohol-mediated redox regulation and form the basis for the adoption of appropriate drinking guidelines.